Fernando Picó. One Frenchman, Four Revolutions: General Ferrand and the Peoples of the Caribbean. Markus Wiener, 2011. - CHRISTIAN LEBRON LEBRON (Vernacular: New Connections in Language, Literature, & Culture, 2024)
Fernando Picó, One Frenchman, Four Revolutions: General Ferrand and the Peoples of the Caribbean (Princeton, NJ: Markus Wiener, 2011). Word Count: 2,689 The book "One Frenchman, Four Revolutions: General Ferrand and the Peoples of the Caribbean" by Fernando Picó delves into the life of General Jean-Louis Ferrand and its connection to the four revolutions unfolding in the Caribbean between 1803 and 1808. Employing an intriguing literary technique, Picó initiates the narrative with the general's death, paving the way to explore the events surrounding the political landscape of the time. Drawing inspiration from Voltaire, the author employs a methodology that reflects the influence of the Enlightenment thinker, emphasizing the geopolitical significance of the Caribbean within the context of the Atlantic Revolution. Picó scrutinizes Ferrand's administration in a revolutionary world, shedding light on overlooked aspects that have been overshadowed and mischaracterized, particularly concerning French and Haitian intervention in Dominican society. The book contributes to Caribbean historiography by offering a comprehensive examination of the era and providing a valuable toolbox for diverse historical perspectives. The author subtly engages with the omission of elements related to the Haitian indigenist project, indirectly favoring a Hispanist stance. While the work is tailored for a more specialized audience, it serves as a notable addition to Caribbean historical scholarship, encouraging varied approaches to historical research.